Google Classroom as a Collaboration Tool For Blended Learning in Vocational Education - Lestari, Nia; Abadi, Agus Haris (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2021)
The vocational learning paradigm is changing in the demands of the current era, it is necessary to change teaching methods that follow changes in industry trends, information systems, education quality and students who have a significant relationship with pedagogical methods and the needs of the world of work. Blended learning is balanced learning. This balance is achieved by combining the advantages of the two learning modalities. It is also clear that the generally accepted concept of blended learning is to combine some aspects of technology with face-to-face learning. Google Classroom offers a core suite of tools that includes the basics of the classroom. This paper focuses on Google Classroom as a collaborative tool in blended learning, combining technology and face-to-face interaction to increase student engagement, streamline assessment and open lines of communication between teachers and students. From several studies that have been carried out through the literature review method. Google Classroom provides similar applications through Google Docs, Sheets and Slides to facilitate e-learning.Keywords: google classroom, collaboration, blended learning, vocation educationDOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202105